Flexural buckling behaviour and design of welded stainless steel box-section beam-columns. (October 2019) - Ning, Keyang; Yang, Lu; Yuan, Huanxin; Zhao, Menghan
Abstract: A comprehensive experimental and numerical study on flexural buckling behaviour of welded stainless steel box-section beam-columns is presented in this paper. A total of ten test specimens were prepared and tested subjected to eccentric compression. The cross-section and length of the test specimens were carefully designed by referring to existing design specifications to be insusceptible to local buckling. The full experimental load versus deformation and load versus strain curves were obtained. Prior to member testing, both material tests and geometric imperfection measurements were conducted and reported in detail. Finite element (FE) models were developed and validated against the obtained beam-column test results afterwards, which were utilised to perform parametric studies on the flexural buckling behaviour, generating sufficient numerical data points. Based on the obtained test and FE results, the design methods provided in EN 1993-1-4+A1 and AISC DG 27 were assessed. It was shown that both EN 1993-1-4+A1 and AISC DG 27 provided generally conservative and scattered predictions for the buckling resistance of welded stainless steel box-section beam-columns. Moreover, a newly revised proposed interaction factor was proposed in the framework of EN 1993-1-4+A1, and strength predictions with reduced scatter were therefore achieved. Highlights: The stainless steel box-section beam-columns were tested subjected to eccentric compression. Finite element models were validated against test results, and employed for parametric studies. The accuracy and reliability of existing design provisions given in EN 1993-1-4+A1 and AISC DG 27 were assessed. A newly revised proposed interaction factor was proposed in the framework of EN 1993-1-4+A1.